Preparation method for efficiently synthesizing hectorite

Through the steps of room temperature mixing and high temperature crystallization, combined with filtration, washing, drying and grinding, the problems of high cost, complex conditions, time and energy consumption in the existing lithium soapstone synthesis methods are solved, and the preparation of lithium soapstone with high purity and excellent performance is achieved.

CN119569071APending Publication Date: 2025-03-07ZHEJIANG KELEI NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411818088.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium soapstone synthesis methods are high cost, complex synthesis conditions, time-consuming and energy-consuming, difficult to separate product particles, and insufficient purity.

Method used

High-efficiency synthetic lithium soapstone is prepared by mixing specific raw materials at room temperature, adjusting pH, performing high-temperature crystallization, and combining filtration, washing, drying and grinding steps.

Benefits of technology

The preparation of lithostone with high purity and excellent performance is achieved, which reduces costs, simplifies synthesis conditions, shortens synthesis time, and improves the rheological performance and application adaptability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569071A_ABST
    Figure CN119569071A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method for efficiently synthesizing hectorite, aiming at the defects that the existing hectorite synthesis technology is high in cost, complex in condition, time-consuming, energy-consuming and the like, process improvement is carried out, and the method comprises the following core steps: adding a magnesium carbonate and magnesium oxide mixed magnesium source, a specific silicon source and a single lithium source into deionized water at room temperature, and carrying out high-speed shearing to obtain uniform slurry; then adjusting the pH value by adopting sulfuric acid, hydrochloric acid, sodium carbonate or introducing a plurality of regulators such as carbon dioxide, and shearing; and performing high-temperature crystallization in a closed container, and sequentially performing filter pressing, washing, drying, grinding and sieving to obtain a finished product. According to the preparation method for efficiently synthesizing hectorite provided by the invention, various cheap raw materials are selected to replace high-purity chemicals, multi-link optimization is realized, the cost is reduced, the efficiency is increased, time is shortened, energy is saved, and the product is excellent in quality, high in purity, few in impurities, excellent in microstructure, dispersed, transparent, high in rheological property and huge in application potential in the fields of cosmetics, well drilling, coatings and the like; the method has breakthrough significance and wide prospects in industrial production and product application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical synthesis, and in particular to a method for preparing highly efficient synthetic hectorite. Background Art

[0002] Hectorite belongs to the montmorillonite family and is a layered silicate clay that is widely used in a variety of industrial sectors. It is used as a thickener in cosmetics and personal care products; in the oil and gas drilling industry, hectorite has better performance than high-purity bentonite; in other fields such as coatings, it is used as an inorganic rheology modifier to improve the performance of fluid systems. Bentonite is abundant in the world, but natural hectorite ore is relatively rare. Most of the hectorite products on the market are artificially synthesized hectorite, which is lighter in color than bentonite, has a lower iron content, a smaller particle size, and has higher rheological efficacy in terms of viscosity and yield stress. The differences in the chemical structure and morphology of the two minerals result in different performance differences. Hectorite has smaller flakes, providing greater expansion capacity and better rheological properties.

[0003] Lithium laponite is a trioctahedral structure, and lithium partially replaces magnesium on the octahedral layer, so that the negative charge generated is neutralized by the interlayer cations. Lithium has a high mobility in the octahedral structure, which can generate more negative charges, so that there are more sodium ions between the layers, the swelling performance is better, and its edge exposure makes it easier to form a card house structure, so that it has high expansion, high viscosity and better thixotropic properties. At present, the synthesis method of hectorite includes using soluble salts such as magnesium chloride, sodium hydroxide, sodium carbonate, lithium fluoride, water glass, etc. as raw materials, mixing and boiling and refluxing at atmospheric pressure for a certain time, and then filtering, washing, drying and grinding to obtain synthetic hectorite. However, the use of soluble salts as raw materials involves the early nucleation and late crystallization processes, the synthesis conditions control requirements are high, and the entire synthesis time is long, usually more than 24 hours. Although the hectorite product obtained from soluble salts as raw materials has high transparency, high-purity soluble chemicals are usually expensive, and a long synthesis time is required to obtain hectorite of suitable size, and the gelation of the precipitation process will make it difficult to separate the product particles from the reaction slurry.

[0004] At present, there are also some methods for synthesizing lithium soapstone that use magnesium oxide, sodium hydroxide, lithium hydroxide, hydrogen fluoride, etc. as raw materials. However, the crystallization time of synthetic lithium soapstone is relatively long, the energy consumption is large, the cost is high, and strict reaction conditions are required to synthesize relatively pure or appropriately sized lithium soapstone products, and impurities are easily generated. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an efficient synthetic hectorite, which solves the problems of high cost, complex synthesis conditions, time and energy consumption, difficulty in separating product particles, and insufficient purity in the existing hectorite synthesis method.

[0006] The preparation method of the high-efficiency synthetic hectorite provided by the present invention effectively solves the problems of high cost, complex conditions, time-consuming and energy-consuming, etc. through a series of steps such as mixing specific raw materials at room temperature, adjusting pH, high-temperature crystallization, filter pressing, washing, drying and grinding, and can produce hectorite with high purity and excellent performance, which has both economic benefits and environmental protection value, and effectively promotes the development of applications in multiple industries.

[0007] A method for preparing a highly efficient synthetic hectorite comprises the following steps: S1 Raw material mixing: At room temperature, two magnesium sources, magnesium carbonate and magnesium oxide, silicon sources such as silicon dioxide, silica sol, sodium silicate, and lithium sources such as lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate, are gradually added into deionized water to dissolve, and rapidly sheared and homogenized for 15-30 minutes to form a uniform slurry. The order of addition is not limited; magnesium carbonate, magnesium oxide and other raw materials are mixed at room temperature and rapidly sheared and homogenized to construct a uniform reaction system for the synthesis of hectorite, laying a material foundation and uniformity premise.

[0008] S2pH adjustment: The pH of the slurry is adjusted to 9-11 by adding regulators such as sulfuric acid, hydrochloric acid, sodium carbonate or passing carbon dioxide gas, and shearing and homogenizing for 30-60 minutes to obtain a homogenized mixture; the pH of the slurry is accurately adjusted with a variety of regulators and sheared and homogenized for a second time to create a suitable reaction pH environment, optimize the microstructure, and ensure smooth synthesis and stable product quality.

[0009] S3 high temperature crystallization reaction: raise the temperature of the homogenized mixture to 160-300°C in a sealed container and maintain it for 3-6 hours to obtain a crystallized slurry; keep the homogenized mixture in a sealed container at high temperature for 3-6 hours to crystallize the homogenized mixture, which promotes the rearrangement of the raw material atoms and crystallizes them into lithium laponite, which determines the crystal structure and properties and is the core key step.

[0010] S4 filtration and washing: After cooling to room temperature, filter the crystallized slurry with a vertical filter press, add water to wash away free ion impurities until the outlet water conductivity is 500-1000μS / cm, and obtain a filter cake; after cooling, vertical filter press and wash the crystallized slurry with water multiple times to a specific conductivity to remove free impurities to obtain a filter cake, purify the lithium soap stone, improve the purity, and ensure the purity of product quality.

[0011] S5 filter cake drying: A tunnel drying device is used to reduce the moisture content of the filter cake to 5-10% to obtain a dried product; the tunnel drying device reduces the moisture content of the filter cake to 5-10% to obtain a dried product, giving the product appropriate humidity and stability, which is convenient for subsequent processing, storage and transportation.

[0012] S6 grinding and sieving: Use a grinding machine to crush the dried product, and the powder fineness reaches 50-70 mesh and is sieved to obtain synthetic lithium soap stone; the grinding machine crushes the dried product to reach the target fineness to obtain the finished product, adjust the product particle size, optimize the use performance and processing adaptability, and meet the needs of different application fields.

[0013] The raw material mixing step of the present invention limits the magnesium source to a mixture of magnesium carbonate and magnesium oxide with a specific molar ratio, the silicon source to water glass with a specific silicon dioxide content and a combination thereof, and the lithium source to one of lithium fluoride and the like, so as to accurately control the raw material composition and proportion, optimize the synthesis reaction path and kinetics of hectorite, synergistically improve the product purity, improve the microstructure and crystal morphology, enhance the rheological properties and dispersibility, ensure the product quality and performance excellence and stability from the source, and expand its adaptability and advantages in multiple fields.

[0014] Preferably, the magnesium source in the raw material mixture of step S1 is a mixture of magnesium carbonate and magnesium oxide, with a molar ratio of 1-3:3-1; the silicon source is water glass, fumed silica, and a mixture of water glass and fumed silica with a silicon dioxide content of 25-30%; the lithium source is one of lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate.

[0015] Magnesium carbonate and magnesium oxide are mixed in a molar ratio of 1-3:3-1 as a magnesium source. The key is to provide appropriate magnesium content and activity, optimize the synthesis reaction rate and the doping and lattice construction of magnesium atoms during the growth of lithium laponite crystals. This ratio can accurately regulate the integrity and stability of the crystal structure, avoid crystal defects or growth disorders caused by a single magnesium source or improper ratio, ensure the regularity of the lithium laponite structure to improve product quality and performance consistency, and stabilize its functional performance in various application scenarios.

[0016] Water glass, fumed silica or a mixture thereof containing 25-30% silica is selected as the silicon source. The silica content and existence form of this type of silicon source are optimized to adapt to the lithium laponite synthesis system. During the reaction, it stably releases silicon elements according to a specific content to participate in the condensation reaction to construct a silicon-oxygen tetrahedral network. This network is the key framework of the lithium laponite layered structure. The precise content ensures moderate cross-linking and extension of the network, giving the lithium laponite ideal mechanical strength, expansion and adsorption characteristics, and is suitable for multiple application functional demands such as cosmetic thickening, drilling fluid suspension, and coating rheology regulation.

[0017] Lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate can be selected as the lithium source. The differences in ion release rate and reaction activity of different lithium sources provide selection space for optimization of synthesis conditions and customization of product performance. Lithium carbonate gently releases lithium ions to adapt to reaction conditions for fine-tuning. The fluoride ion dissolution and hydrolysis of lithium fluoride can optimize crystal nucleation growth, improve transparency and structural stability, but involves environmental considerations. The strong alkalinity and high activity of lithium hydroxide affect the product purity and microstructural order. Users can flexibly select lithium sources according to the focus of product performance, accurately shape the microstructure and macroscopic performance of lithium soapstone, and expand application flexibility and pertinence.

[0018] The pH adjustment step of the present invention accurately controls the rate and time of dripping sulfuric acid, hydrochloric acid and sodium carbonate solution or introducing carbon dioxide gas, and continuously stirs to accurately adjust the pH of the slurry to 9-11, thereby creating an acid-base environment suitable for the synthesis of hectorite, stabilizing the ion activity of the raw materials, optimizing the rate and direction of the condensation hydrolysis reaction, ensuring orderly crystal nucleation growth, regular microstructure, improved product purity and excellent key performance such as rheological properties, enhancing the controllability of the synthesis process and the stability of product quality, and broadening the application prospects.

[0019] Preferably, the pH adjustment in step S2 is performed by slowly dropping the prepared sulfuric acid, hydrochloric acid or sodium carbonate solution into the slurry after the raw materials are mixed and stirring, or by introducing carbon dioxide gas at a rate of 10-50 mL / min for 3-8 minutes and maintaining a certain stirring speed until the pH value of the slurry is adjusted to 9-11.

[0020] Accurately adjust the slurry pH to 9-11 to create appropriate pH conditions. Within this range, the ionic activity and reaction activity of each raw material in the synthesis of hectorite reach the best balance; excessive acidity will hinder the hydrolysis of the silicon source, and excessive alkalinity will cause magnesium precipitation. Appropriate pH can avoid such problems, ensure smooth and efficient progress of the reaction, and consolidate the foundation of product quality.

[0021] Specific pH affects the nucleation growth rate and direction of hectorite crystals. Moderate alkalinity promotes the orderly condensation of silicon-oxygen tetrahedrons and magnesium octahedrons, constructs a regular layered lattice structure, reduces the probability of crystal defect generation, improves product crystallinity and purity, and optimizes the microstructure to give the product excellent performance.

[0022] Stabilizing pH ensures the uniformity of the reaction system, prevents local over-acidity or over-alkalinity from causing component segregation and agglomeration, allows the raw materials to participate in the reaction evenly, ensures uniform and stable product performance, and stably performs its functions in various application fields, such as uniform thickening of cosmetics and rheological stability of coatings, thereby improving product market competitiveness and application reliability.

[0023] The preparation process of the lithium soapstone of the present invention includes two shearing and homogenizing operations. The first time, when the raw materials are mixed, the high speed of 1000-3000rpm is used to disperse and dissolve the raw materials, break up agglomerations, strengthen dispersion, and lay the foundation for uniform reaction; the second time, after pH adjustment, the speed of stirring is 500-1500rpm and the direction is changed at the right time to further homogenize the slurry, refine the particles, promote the interaction of components, improve the stability and uniformity of the system, and synergistically optimize the lithium soapstone synthesis reaction process, microstructure and product quality consistency, and enhance performance reliability and application universality.

[0024] Preferably, the shear homogenization operation is applied twice, the first shear homogenization is performed in step S1 raw material mixing, using a high-speed shear disperser to stir and shear the deionized water solution of the dissolved raw materials at a speed of 1000-3000 rpm; the second shear homogenization is performed in step S2 pH adjustment, using a high-speed shear disperser to stir and shear the slurry added with the regulator at a speed of 500-1500 rpm, and after 15-20 minutes, the stirring direction is changed and stirring is continued to obtain a homogenized mixture.

[0025] The first shear homogenization of the present invention is carried out at the S1 raw material mixing stage, with a high-speed shear of 1000-3000rpm, to strongly break up the agglomerates that may be formed by raw materials such as magnesium carbonate, magnesium oxide, silicon source and lithium source in deionized water. This operation makes the particles of each raw material fully dispersed, greatly increases the contact area and collision probability between the raw materials, ensures that the subsequent reactions are carried out uniformly and synchronously, lays a foundation for uniform material distribution for synthesizing high-purity and uniform-performance lithium soapstone, and avoids product quality fluctuations caused by excessive or insufficient local reactions.

[0026] In the S2 pH adjustment stage of secondary shear homogenization, after pH adjustment, the slurry is stirred at a speed of 500-1500rpm and the direction is changed in the middle to deeply optimize the uniformity of the system; on the one hand, it continuously refines the tiny particle aggregates or uneven areas that may be produced by pH changes to improve the physical stability of the system; on the other hand, it promotes the full integration of the regulator and the raw materials, accelerates the achievement of chemical reaction balance, makes the formation of lithium soapstone crystal nuclei and the growth environment more uniform and stable, and accurately regulates the orderliness of the crystal microstructure and the consistency of product quality, ensuring that the product can stably perform its functions in multiple application scenarios such as cosmetic thickening and drilling fluid modification.

[0027] The high-temperature crystallization step of the present invention is carried out in a Teflon or stainless steel reactor with stirring, and the pretreated homogenized mixture is crystallized at high temperature, thereby constructing a high-temperature and high-pressure closed environment and accurately controlling the temperature and timing, stimulating the activity of raw material atoms, accelerating the orderly growth and structural improvement of the lattice, improving the crystallinity, purity and stability of lithium soapstone, optimizing the micro-layered structure and rheological properties, ensuring that the product quality meets the stringent standards of multiple industries, and promoting its industrial-scale production and high-end application expansion.

[0028] Preferably, the high temperature crystallization reaction in step S3 is carried out in a closed container Teflon reactor or a stainless steel reactor with stirring, and the homogenized mixture after raw material mixing, pH adjustment and shear homogenization treatment is heated to 160-300° C. and maintained at this temperature for 3-6 hours.

[0029] The high temperature crystallization lasts for 3-6 hours in a closed environment at 160-300℃, providing energy for the rearrangement and crystallization of atoms and ions in the homogenized mixture. During this high temperature period, the hectorite crystals grow in an orderly manner according to the thermodynamic equilibrium rules, and the silicon-oxygen tetrahedrons and magnesium octahedra are precisely stacked into a regular layered structure, repairing lattice defects, improving crystallinity, and strengthening structural stability and integrity, laying the foundation for the excellent performance of the product. For example, the long-lasting thickening in cosmetics and the efficient suspension of drilling fluids rely on this stable structure.

[0030] High temperature drives the migration, volatilization or reaction transformation of impurity atoms, and separates them from pure lithium laponite crystals to effectively purify the products. Precise temperature control and timing ensure that each batch of products undergoes the same thermal history, stabilizes the atomic migration rate and reaction degree, and makes the microstructure, crystal size and distribution uniform. The batch-to-batch differences in product purity and performance are extremely small, which meets the needs of large-scale stable production in industry and ensures stable performance in different application scenarios.

[0031] High-temperature crystallization profoundly changes the physical and chemical properties of hectorite. It enhances the interlayer force and optimizes the expansion, adsorption, and rheological properties; it adjusts the charge distribution and the number of active sites on the crystal surface, improves the dispersibility and compatibility in complex systems, and is of great significance in the precise control of rheological properties of coatings and the shaping of delicate textures of cosmetics, expanding the high-end application potential of products and enhancing market competitiveness and added value.

[0032] The filter pressing and washing step of the present invention uses precise pressure flow rate to filter the crystallized slurry to efficiently separate the solid and liquid to obtain a filter cake, and washes the filter cake with a small amount of water in proportion for multiple times to fully remove free impurities, thereby synergistically achieving efficient purification of hectorite and deep removal of impurities, stabilizing the high purity quality of the product, ensuring its stable and reliable performance and precise function in multiple applications such as cosmetic thickening and drilling fluid improvement, and improving the overall quality and market value of the product.

[0033] Preferably, the pressure of the filter press in step S4 is 0.05-0.2MPa, and the flow rate is controlled at 100-500mL / min; the amount of water used for washing is calculated as 5-10 times the volume of the filter cake based on the hectorite output and impurity content, and is washed in small amounts for 3-5 times, and the filter cake is rinsed and soaked with an appropriate amount of water each time for 5-10 minutes before filter pressing.

[0034] The filter press process can achieve efficient solid-liquid separation and impurity removal. The filter press pressure is precisely controlled at 0.05-0.2MPa and the flow rate is 100-500mL / min. Under the premise of ensuring the integrity of the hectorite particles, the solid hectorite in the crystallized slurry and the impurity-containing filtrate are efficiently separated according to the appropriate pressure difference and flow rate. This operation prevents the particles from breaking due to excessively high pressure or the filtration from being slow and blocked due to too low pressure, quickly obtains the filter cake, and preliminarily removes a large amount of free impurities, laying the foundation for subsequent deep purification, ensuring the basic purity of the product, and preventing impurities from interfering with the product performance, such as avoiding affecting the fineness of cosmetics and the stability of drilling fluids.

[0035] Deep purification and quality optimization in the washing process. Customize the filter cake according to the output impurities with 5-10 times the volume of water, rinse, soak and filter press 3-5 times in small amounts, to achieve gradient elution of impurities; small amounts and multiple times improve the contact and exchange efficiency between washing water and impurities, fully dissolve and remove impurities adsorbed in the pores and surface of the filter cake, and prevent a single large amount of water from causing re-adsorption of impurities or loss of lithium soapstone. Precise washing and deep purification of products significantly improves purity and optimizes microstructure, ensuring excellent and stable performance of products in various industries, such as precise control of coating rheology, safe and long-term thickening of cosmetics, and enhancing product market competitiveness and application adaptability.

[0036] The filter cake drying step of the present invention accurately controls the drying conditions for the parameter setting of the tunnel drying device, gently removes moisture while stabilizing the microstructure and physicochemical properties of the lithium soapstone, and gives the product a suitable humidity for easy storage, transportation, and processing, ensuring stable performance, reliable quality, and continuous function when used in the fields of cosmetics, drilling, coatings, etc., thereby improving the industrial application value and market adaptability of the product.

[0037] Preferably, in the step S5, the temperature of the tunnel drying device in the filter cake drying is set at 80-150°C, the drying time is 4-12 hours, the air flow velocity is maintained at 1-3 m / s, and the moisture content of the obtained dried product is 5-10%.

[0038] Drying in a moderate temperature range of 80-150℃ for 4-12 hours can accurately remove the moisture of the filter cake to 5-10%, avoiding high temperature from destroying the layered lattice structure and surface active groups of the hectorite. This process finely balances water evaporation and structural stability according to the set temperature and time, maintains the integrity and microscopic order of the crystal, ensures the structural stability of the product during storage, processing and application, and guarantees the thickening stability of cosmetics, the suspension durability of drilling fluids and the rheological reliability of coatings.

[0039] Stable airflow speed of 1-3m / s coordinates drying, accelerates water mass transfer while preventing local overheating and unevenness, and optimizes product processing performance and storage characteristics; suitable moisture content gives the product ideal processing plasticity and prevents agglomeration, facilitating subsequent grinding and multi-field formulation; improves storage stability, prevents microbial growth and chemical deterioration, extends shelf life, ensures constant product quality from production to use, reduces logistics and warehousing loss risks, and expands market circulation radius and commercial value realization space.

[0040] The grinding and screening steps of the present invention accurately control the crushing parameters to optimize the particle size distribution of hectorite, increase the specific surface area and reaction activity of the powder, enhance the dispersibility, compatibility and functionality in application scenarios such as cosmetic thickening, drilling fluid improvement, and coating modification, ensure that the product has good processing adaptability and excellent use effect, meet the needs of industrialized fine production and the quality standards of multiple industries, and expand the breadth and depth of market applications.

[0041] Preferably, the grinding speed of the grinding and screening in step S6 is maintained at 1000-5000 rpm for 5-30 minutes, and the feed rate is 5-20 kg / hour until the powder fineness reaches 50-70 mesh and can be screened.

[0042] Run at a speed of 1000-5000 rpm for 5-30 minutes, combined with a feed rate of 5-20 kg / hour, and finely grind and dry the product to 50-70 mesh for sieving. This precise operation makes the hectorite particles refined and the particle size distribution narrow, increases the specific surface area, and improves the surface energy and activity. It accelerates the hydration and thickening response when thickening cosmetics, enhances the interaction between particles in drilling fluids and optimizes suspension, and promotes pigment dispersion in coatings to improve covering and leveling, comprehensively improves product application performance, and expands functional space.

[0043] Specific grinding and screening parameters ensure product quality consistency and processing adaptability. Stable particle size fits the processing technology window of various industries, accurately controls the texture of cosmetics production, stabilizes the rheology of drilling fluids, and ensures dispersion and film formation in coatings manufacturing, preventing quality fluctuations and process failures caused by particle size fluctuations, ensuring uniform particle size of multiple batches of products, and consolidating product market reputation, laying a solid foundation for large-scale industrialized stable production and meeting diversified market needs, and enhancing the product's full life cycle value and industry competitiveness.

[0044] The preparation method of the high-efficiency synthetic lithium soap stone of the present invention has significant advantages. It adopts a mixed magnesium source, a specific silicon-lithium source and an innovative process. The room temperature mixing reduces the cost, the multi-element pH adjustment is environmentally friendly and green, the precise crystallization and efficient post-processing improve the quality and performance. The product has high purity, excellent structure and good rheology, which promotes the industrial-scale production of lithium soap stone, enhances market competitiveness, injects strong impetus into the application of cosmetics, drilling, coatings and other industries, and has both economic and environmental benefits.

[0045] In summary, the present invention has the following beneficial effects: 1. Compared with the existing preparation process, the raw materials of the present invention use a mixed magnesium source, a silicon source and a lithium source for rapid shearing and homogenization at room temperature, and relatively cheap raw materials such as magnesium carbonate and magnesium oxide are selected to replace part of high-purity soluble chemicals, which significantly reduces the cost of raw materials; at the same time, the synthesis effect is improved, the synthesis time is shortened, the energy consumption is reduced, the equipment loss and operating costs are reduced, the economic benefits are improved, and the market competitiveness of the products is enhanced; 2. The overall synthesis method of the present invention improves product quality while shortening reaction time and reducing costs. The overall efficiency is far superior to traditional methods. The synthesis process is simple and compact, the reaction conditions are easy to control, and steps such as room temperature mixing and specific temperature crystallization do not require complex equipment and strict environmental parameters. In addition, each link is closely connected and time-consuming, which effectively promotes large-scale industrial production. 3. The diversified raw materials of the present invention optimize the synthesis conditions to obtain excellent product performance. The prepared hectorite has high purity, few impurities, a microscopic lamellar structure, excellent dispersibility, high transparency, high instant transparency, good rheological properties such as sol viscosity and yield stress, and excellent performance in application scenarios such as cosmetic thickening, drilling fluid performance improvement, and coating modification; 4. The present invention provides a variety of pH adjusting agents to choose from, including sulfuric acid, hydrochloric acid, sodium carbonate, CO2, etc., which can adapt to different production conditions. Among them, the method of adjusting pH by introducing CO2 is simple, safe and efficient, which is a reflection of process innovation, avoiding the risk of using dangerous or controlled reagents such as sulfuric acid, reducing environmental pollution, and conforming to the concept of green chemistry. At the same time, the selection of raw materials reduces harmful emissions and reduces environmental pressure from the source. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a process flow diagram of a method for preparing highly efficient synthetic hectorite; Figure 2 It is a schematic diagram of the yield stress of synthetic hectorite with different lithium sources; Figure 3 It is a schematic diagram of the yield stress of synthetic hectorite with different silicon sources; Figure 4 It is a schematic diagram of the yield stress of synthetic hectorite with different magnesium carbonate / magnesium oxide ratios; Figure 5 It is a schematic diagram of the yield stress of synthetic hectorite using different pH adjusters; Figure 6 is a schematic diagram of the X-ray diffraction pattern of the synthetic hectorite of Example 7; Figure 7 is a schematic diagram of the X-ray diffraction spectrum of the synthetic hectorite of Comparative Example 1; Figure 8 is a schematic diagram of a scanning electron microscope image of the synthetic hectorite of Example 7; Fig. 9 This is a schematic diagram comparing the yield stress of different synthetic lithium laponites. DETAILED DESCRIPTION

[0047] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0048] Example 1

[0049] S1 raw material mixing: weigh a silicon source containing 0.45 mol of silicon dioxide, add it to 500g of deionized water, stir evenly, then add a lithium salt containing 0.062 mol of lithium and stir to dissolve; weigh 0.18 mol of magnesium carbonate and magnesium oxide respectively, add them to the mixture, and shear and disperse for 20 minutes; S2 pH adjustment: 96% sulfuric acid adjusts the pH to about 10, and shears and homogenizes for 1 hour; S3 high temperature crystallization reaction: transfer the homogenized mixture to a Teflon reactor and heat it to 200°C for 6 hours. After the reaction is completed, cool it to room temperature. S4 filtration and washing: the slurry is filtered through a vertical filter press and washed with water until the effluent conductivity is less than 1000 μS / cm; S5 filter cake drying: The obtained filter cake is dried in a tunnel until the moisture content is less than 10%; S6 grinding and sieving: crush the dried product with a grinding machine and pass it through a 60-mesh sieve to obtain the synthetic hectorite.

[0050] The synthesis conditions of Examples 1-9 are shown in Table 1 below. The silicon source is water glass (silicon dioxide content is about 27%), fumed silica, and a mixture of water glass and fumed silica; the lithium source is one of lithium carbonate, lithium hydroxide monohydrate and lithium fluoride.

[0051] Table 1 Synthesis conditions of Examples 1-9

[0052] Example 10 S1 Raw material mixing: weigh 400g water glass, add it into 2kg deionized water, stir evenly, then add 9.2g lithium carbonate and stir to dissolve; weigh 60.192g magnesium carbonate and 29.304g magnesium oxide respectively, add them into the mixture, and shear and disperse for 20min; S2 pH adjustment: Pass carbon dioxide gas through the blades for about 5 minutes to make the slurry pH close to 10, and then continue shear dispersion for 1 hour; S3 high temperature crystallization reaction: transfer the homogenized mixture to a stainless steel reactor with stirring and heat it to 200°C for 3 hours. After the reaction is completed, cool it to room temperature. S4 filtration and washing: the slurry is filtered through a vertical filter press and washed with water until the effluent conductivity is less than 1000 μS / cm; S5 filter cake drying: The obtained filter cake is dried in a tunnel until the moisture content is less than 10%; S6 grinding and sieving: crush the dried product with a grinding machine and pass it through a 60-mesh sieve to obtain the synthetic hectorite.

[0053] Comparative Example 1 S1 raw material mixing: weigh 350 g magnesium chloride as a magnesium source, add water to a homogenizing container, stir and dissolve, and heat to 80°C; weigh 10 g lithium carbonate as a lithium source, dissolve in water, add to a homogenizing container, and stir evenly; weigh 130 g Na salt, dissolve in water, slowly add to a homogenizing container, and stir for 30 min-2 h; weigh 500 g water glass as a silicon source, add to a homogenizing container, continue stirring, and mix the three evenly to obtain a mixed material; S2 pH adjustment: Use sodium hydroxide to adjust the pH to between 11-12, and the total mass concentration of the mixed material is 30%; S3 high temperature crystallization reaction: transfer the homogenized mixture to a stainless steel reactor and heat it to 180°C for 12 hours. After the reaction is completed, cool it to room temperature. S4 filtration and washing: the slurry is filtered through a vertical filter press and washed with water until the effluent conductivity is less than 1000 μS / cm; S5 filter cake drying: The obtained filter cake is dried in a tunnel until the moisture content is less than 10%; S6 Grinding and sieving: Use a grinding machine to crush the dried product and pass it through a 60-mesh sieve to obtain hectorite.

[0054] Comparative Example 2 S1 raw material mixing: weigh a silicon source containing 0.45 mol of silicon dioxide, add it to 500g of deionized water, stir evenly, then add a lithium salt containing 0.062 mol of lithium and stir to dissolve; weigh 0.18 mol of magnesium carbonate and magnesium oxide respectively, add them to the mixture, and shear and disperse for 20 minutes; S2 High temperature crystallization reaction: transfer the homogenized mixture to a Teflon reactor and heat it to 200°C for 6 hours. After the reaction is completed, cool it to room temperature. S3 filtration and washing: the slurry is filtered through a vertical filter press and washed with water until the effluent conductivity is less than 1000μS / cm; S4 filter cake drying: The obtained filter cake is dried in a tunnel until the moisture content is less than 10%; S5 grinding and sieving: crush the dried product with a grinding machine and pass it through a 60-mesh sieve to obtain the synthetic hectorite.

[0055] Comparative Example 3 Commercially available hectorite product Laponite RD.

[0056] The relevant properties of the synthetic hectorite of Examples 1-10 and Comparative Examples 1-3 were compared, and the results are shown in Table 2 below.

[0057] Table 2 Comparison of the performance of synthetic hectorite products in Examples 1-10 and Comparative Examples 1-3

[0058] From products 1-3, i.e., embodiments 1-3, it can be obtained that the present invention uses different lithium sources to synthesize hectorite, as shown in Table 2 and Figure 2 The yield stress diagram of different lithium sources for synthesizing hectorite shows that lithium carbonate, lithium fluoride and lithium hydroxide can all successfully synthesize hectorite. After 3% dispersion liquid is left to stand for 24 hours, it can form gel and has good yield stress. The hectorite synthesized by lithium carbonate has higher transparency when dispersed in water; the hectorite synthesized by lithium hydroxide has the highest yield stress although its transparency is relatively low; the hectorite synthesized by lithium fluoride has good transparency and yield stress. The introduction of fluoride ions promotes the synthesis of hectorite, such as regulating dissolution, hydrolysis, condensation and dehydroxylation, thereby nucleating and growing into hectorite crystals. Fluoride ions promote the dissolution and hydrolysis of silicon dioxide. In addition, fluoride ions partially replace the hydroxyl groups in the hectorite layer and produce defects in the lattice. However, using lithium fluoride as a raw material may involve the discharge of fluoride-containing wastewater, causing environmental pollution.

[0059] From products 1, 4, and 5, namely, examples 1, 4, and 5, the present invention uses different silicon sources to synthesize hectorite, as shown in Table 2 and Figure 3 The yield stress diagram of hectorite synthesized from different silicon sources shows that water glass or a mixture of silicon dioxide and water glass can be used as a silicon source to synthesize dispersed and transparent hectorite, while when pure silicon dioxide is used as a silicon source, under the same reaction conditions, the synthesized hectorite is difficult to disperse, precipitates at the bottom, and is difficult to form a gel. Only the hectorite synthesized from water glass has a good yield stress.

[0060] From products 1, 6, and 7, namely, examples 1, 6, and 7, the present invention compares the synthesis of hectorite with different magnesium carbonate / magnesium oxide molar ratios. Figure 4 From the yield stress diagram of synthesized hectorite with different magnesium carbonate / magnesium oxide ratios, it can be seen that all three ratios can synthesize hectorite that can form gel, and the yield stress is not much different, but when the magnesium carbonate / magnesium oxide molar ratio is 1:1, the dispersion has the best transparency.

[0061] From products 1, 8, 9, and 12, namely, Examples 1, 8, 9, and Comparative Example 2, it can be seen that the present invention investigates the effects of different pH regulators on the performance of hectorite products. Figure 5It is known from the yield stress diagram of the synthetic hectorite using different pH adjusting agents that the transparency of the hectorite synthesized without adjusting the pH is not high, but its gel has the highest yield stress. In the case of not adjusting the pH, the decomposition rate of raw material magnesium oxide or magnesium carbonate is slow, and the synthesized hectorite lamella is larger, enabling it to form a network structure faster, but it is precisely because of its large lamellae that it is difficult to disperse completely, resulting in its lower transparency. The hectorite transparency synthesized when sulfuric acid is used to adjust pH is the best, and its lamellae are small and easy to disperse, but because sulfuric acid is a control reagent, and in a large number of production processes, it is highly required for equipment, and the safety during use is also difficult to guarantee. Therefore, the present invention uses the mode of passing carbon dioxide gas to adjust pH, and in Example 9, only 5min of carbon dioxide gas is passed into the slurry, and the hectorite with 80% transparency can be obtained.

[0062] From the comparison of products 9, 10, 11, and 13, it can be seen that Example 10 is a 4-fold experiment based on Example 9, and the pH is conditioned by passing carbon dioxide gas for 5 minutes, and a hectorite product with good transparency and yield stress can also be successfully synthesized. Figure 6 The X-ray diffraction pattern of the synthetic hectorite in Example 7 shows that the hectorite synthesized by this method is relatively pure, no impurity peaks are found, and the peak shape is similar to Figure 7 The X-ray diffraction pattern of the salt-processed hectorite of Comparative Example 1 is consistent; Figure 8 The scanning electron microscope image of Example 7 shows that the synthetic hectorite has a lamellar structure. Fig. 9 The comparison chart of yield stress of different synthetic hectorite shows that the hectorite synthesized in Example 7 has similar performance to the salt-process synthetic hectorite in Comparative Example 1 and the commercial Laponite in Comparative Example 3.

[0063] In general, the specific implementation method of the preparation method of a high-efficiency synthetic hectorite of the present invention has closely coordinated and interconnected steps, and through the fine control of the process conditions, it finally achieves the goal of efficiently synthesizing high-quality, high-performance hectorite products that can be widely used in multiple fields, and is higher than commercially available products in some performance areas.

Claims

1. A method for preparing a highly efficient synthetic hectorite, characterized in that: The specific steps include: S1 raw material mixing: two magnesium sources, magnesium carbonate and magnesium oxide, silicon sources such as silicon dioxide, silica sol, sodium silicate, and lithium sources such as lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate, are gradually added into deionized water at room temperature to dissolve, and rapidly sheared and homogenized for 15-30 minutes to form a uniform slurry. The order of addition is not limited; S2 pH adjustment: adjust the pH of the slurry to 9-11 by adding a regulator such as sulfuric acid, hydrochloric acid, sodium carbonate or passing carbon dioxide gas, and shear homogenize for 30-60 minutes to obtain a homogenized mixture; S3 high temperature crystallization reaction: heating the homogenized mixture to 160-300°C in a sealed container and maintaining the temperature for 3-6 hours to obtain a crystallized slurry; S4 filtration and washing: After cooling to room temperature, filter the crystallized slurry with a vertical filter press, add water to wash away free ion impurities until the effluent conductivity is 500-1000 μS / cm, and obtain a filter cake; S5 filter cake drying: use tunnel drying device to reduce the moisture content of filter cake to 5-10% to obtain dried product; S6 Grinding and sieving: Use a grinding machine to crush and sieve the dried product, and the powder fineness reaches 50-70 mesh to obtain synthetic hectorite.

2. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: The magnesium source in the raw material mixture of step S1 is a mixture of magnesium carbonate and magnesium oxide, with a molar ratio of 1-3:3-1; the silicon source is water glass, fumed silica, and a mixture of water glass and fumed silica with a silicon dioxide content of 25-30%; the lithium source is one of lithium fluoride, lithium carbonate, and lithium hydroxide monohydrate.

3. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: The pH adjustment in step S2 is carried out by slowly adding the prepared sulfuric acid, hydrochloric acid or sodium carbonate solution to the slurry after the raw materials are mixed and stirring, or by introducing carbon dioxide gas at a rate of 10-50 mL / min for 3-8 minutes and maintaining a certain stirring speed until the pH value of the slurry is adjusted to 9-11.

4. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: The shear homogenization operation is applied twice. The first shear homogenization is performed in step S1 raw material mixing, and the deionized water solution in which the raw materials are dissolved is stirred and sheared at a speed of 1000-3000 rpm using a high-speed shear disperser; the second shear homogenization is performed in step S2 pH adjustment, and the slurry to which the regulator is added is stirred and sheared at a speed of 500-1500 rpm using a high-speed shear disperser. After 15-20 minutes, the stirring direction is changed and stirring is continued to obtain a homogenized mixture.

5. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: The high temperature crystallization reaction in step S3 is carried out in a closed container Teflon reactor or a stainless steel reactor with stirring, and the homogenized mixture after raw material mixing, pH adjustment, and shear homogenization treatment is heated to 160-300° C. and maintained at this temperature for 3-6 hours.

6. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: The pressure of the filter press in step S4 is 0.05-0.2MPa, and the flow rate is controlled at 100-500mL / min; the amount of water used for washing is calculated to be 5-10 times the volume of the filter cake according to the hectorite output and impurity content, and the washing is carried out in small amounts for 3-5 times, and the filter cake is rinsed and soaked with an appropriate amount of water each time for 5-10 minutes before filter pressing.

7. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: In the step S5 of drying the filter cake, the temperature of the tunnel drying device is set at 80-150° C., the drying time is 4-12 hours, the air flow velocity is maintained at 1-3 m / s, and the moisture content of the obtained dried product is 5-10%.

8. The method for preparing a highly efficient synthetic hectorite according to claim 1, characterized in that: In the step S6, the grinding speed is maintained at 1000-5000 rpm for 5-30 minutes, and the feed rate is 5-20 kg / hour until the powder fineness reaches 50-70 mesh sieve.

Citation Information

Cited By

  • Flexible hectorite / polyurethane composite film and preparation method thereof

    CN120441889A